Mathematical Modeling and Theoretical Analysis of Bioconvective Magnetized Sutterby Nanofluid Flow Over Rotating Disk with Activation Energy - Haq, Fazal; Rahman, Mujeeb Ur; Khan, M. Ijaz; Abdullaeva, Barno Sayfutdinovna; Altuijri, Reem (BioNanoScience, 2023)
In this article, flow behavior of magnetized Sutterby nanoliquid due to rotating permeable disk is investigated. Suspended solid nanoparticles are stabilized with the help of bioconvection and buoyancy forces. Energy and concentration relations are respectively modeled taking thermal radiation and Arrhenius energy. Additionally, binary chemical reaction in nanomaterial flow is accounted. Flow governing radiated Sutterby nanomaterial is expressed by dimensional equations using boundary layer suppositions. Using appropriate transformations, the dimensional system is altered to a nondimensional one. The nondimensional governing equations are solved via Runge–Kutta-Fehlberg method (RKF-45). The effective consequences of diverse flow regulating variables on fluid velocity, thermal field, mass concentration, and motile microorganisms density are studied via various curves. Surface drag force, heat transfer, density number, and Sherwood number are computed numerically and analyzed. It is observed that velocity components diminished versus rising Hartman number, Reynolds number, fluid material variable, and porosity parameter. Further, it is observed that chemical reaction and activation energy have opposite impacts on mass concentration. Major observations of current exploration are itemized at the end.